A multipurpose natural and renewable polymer in medical applications: Bacterial cellulose - de Oliveira Barud, Hélida Gomes [UNESP]; da Silva, Robson Rosa [UNESP]; da Silva Barud, Hernane [UNESP]; Tercjak, Agnieszka; Gutierrez, Junkal; Lustri, Wilton Rogério; de Oliveira, Osmir Batista [UNESP]; Ribeiro, Sidney J.L. [UNESP] (Elsevier, 2016)
Bacterial cellulose (BC) produced by some bacteria, among them Gluconacetobacter xylinum, which secrets an abundant 3D networks fibrils, represents an interesting emerging biocompatible nanomaterial. Since its discovery BC has shown tremendous potential in a wide range of biomedical applications, such as artificial skin, artificial blood vessels and microvessels, wound dressing, among others. BC can be easily manipulated to improve its properties and/or functionalities resulting in several BC based nanocomposites. As example BC/collagen, BC/gelatin, BC/Fibroin, BC/Chitosan, etc. Thus, the aim of this review is to discuss about the applicability in biomedicine by demonstrating a variety of forms of this biopolymer highlighting in detail some qualities of bacterial cellulose. Therefore, various biomedical applications ranging from implants and scaffolds, carriers for drug delivery, wound-dressing materials, etc. that were reported until date will be presented.
Keywords: Bacterial cellulose; Biopolymers; Nanocomposites; Tissue engineering; Tissue scaffolds; Wound healing